Factors that influence the indication of a public federal education institution by its students through buzz marketing [doi: 10.21529/RECADM.2016003] - Hildo Anselmo Galter Dalmonech; Marko Aurélio Goularte; Paulo Ferrare Ramos; Danilo Soares Monte-Mor (Revista Eletrônica de Ciência Administrativa, 2017)
This research seeks to identify factors that influence the indication of a Public Federal Institution of Education by its students through buzz marketing. In order to achieve this purpose, a quantitative, descriptive and cross-sectional research was conducted, with primary data collection. The sample consisted of 528 students enrolled in high school, in integrated courses at the Federal Institute of Education, Science and Technology of Espírito Santo´s state. The results show that satisfaction and the buzz marketing behavior are variables that influence the indication of the service of a Federal Public Institution of Education by students. Academically speaking, this study contributes in the sense that expands the knowledge of the buzz marketing action behavior in the area of public education that still is not very known in Brazil, enabling further investigations on the subject. As a practical contribution, this article suggests that managers from public institutions of education can use these results for future decision-making with concerning on projects and public policies related to the recruitment of students.   Keywords Buzz marketing; Quality; Satisfaction; Reputation.